ANALISIS FAKTOR - FAKTOR YANG BERPENGARUH TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2015 – 2017 - Rahman Kurnianto, 15.05.52.0223; Wardjono, Wardjono (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the effect of asset growth, firm size, leverage, and liquidity on profitability in manufacturing companies listed on the Indonesia stock exchange for the period 2015-2017.The population in this study are all Manufacturing Companies Registered on the Stock Exchange of the 2015-2017 Period. The sample selection uses a purposive sampling method. The analytical tool used in this study is multiple linear regression analysis.The test results show that asset growth, company size, and liquidity have a significant positive effect on profitability. While leverage does not have a significant negative effect on profitability.